1994
DOI: 10.1557/proc-364-937
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Creep in Ductile-Phase Toughened Nb5Si3/Nb In-Situ Composites

Abstract: The primary and steady-state creep behavior of ductile-phase toughened Nb5Si3/Nb in-situ composites has been simulated using analytical and finite element (FE) continuum techniques. The microstructure of these composites is complex, consisting of large, elongated primary dendrites of the ductile (Nb) solid-solution phase in a eutectoid matrix with the silicide as the continuous phase. This microstructure has been idealized to facilitate the modeling; the effects of these idealizations on the predicted composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The Nb 5 Si 3 creep rates are much lower than those for the Nb-based solid solutions and are similar to those for the high-Si quaternary alloys. In order to develop a better understanding of the response of the composite to increasing silicide volume fraction and increasing stress, the constitutive behavior of the composite was simulated using the expressions provided by Henshall et al [8,9], where A σ is the applied stress, n is the stress exponent for the silicide (1.0), and m is the stress exponent for the Nb (2.9). s V and w V are the volume fractions of the silicide and Nb, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Nb 5 Si 3 creep rates are much lower than those for the Nb-based solid solutions and are similar to those for the high-Si quaternary alloys. In order to develop a better understanding of the response of the composite to increasing silicide volume fraction and increasing stress, the constitutive behavior of the composite was simulated using the expressions provided by Henshall et al [8,9], where A σ is the applied stress, n is the stress exponent for the silicide (1.0), and m is the stress exponent for the Nb (2.9). s V and w V are the volume fractions of the silicide and Nb, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Parametric modeling has indicated that the creep properties of these composites are insensitive to volume fraction of metallic phase (Henshall et al, 1995), although the experimental data do not completely support this proposal. The role of the volume fraction of silicide in controlling composite creep behavior is shown in Figure 14, which shows the effect of stress on secondary creep rate for a range of quaternary alloy composites with Si concentrations from 12 to 22%.…”
Section: Creep Behaviormentioning
confidence: 90%